2022
DOI: 10.1007/s11587-022-00700-w
|View full text |Cite
|
Sign up to set email alerts
|

Transmuted lower record type inverse rayleigh distribution: estimation, characterizations and applications

Abstract: This study introduces a new lifetime distribution called the transmuted lower record type inverse Rayleigh which extends the inverse Rayleigh distribution and has the potential to model the recovery times of Covid-19 patients.The new distribution is obtained using the distributions of the first two lower record statistics of the inverse Rayleigh distribution. We discuss some statistical inferences and mathematical properties of the suggested distribution. We examine some characteristics of the proposed distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…When the data on COVID-19 recovery time (dataset 4) were fitted to the GMO-EE distribution, the mean recovery time of male patients aged >60 years was estimated to be 18.35 days. Based on the same dataset, Tanış [ 47 ] estimated the mean recovery time to be about 21 days, while Voinsky et al [ 48 ] reported an average recovery time of approximately 15 days for another sample of male COVID-19 patients over the age of 60 years (n = 582) and Barman et al [ 49 ] obtained the 95% confidence interval for average recovery time of 16 to 34 days based on another sample of COVID-19 patients (n = 221). The probability of recovery within 2 weeks was calculated as 44.62% based on the GMO-EE distribution, while Tanış [ 47 ] found it to be 45.25%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When the data on COVID-19 recovery time (dataset 4) were fitted to the GMO-EE distribution, the mean recovery time of male patients aged >60 years was estimated to be 18.35 days. Based on the same dataset, Tanış [ 47 ] estimated the mean recovery time to be about 21 days, while Voinsky et al [ 48 ] reported an average recovery time of approximately 15 days for another sample of male COVID-19 patients over the age of 60 years (n = 582) and Barman et al [ 49 ] obtained the 95% confidence interval for average recovery time of 16 to 34 days based on another sample of COVID-19 patients (n = 221). The probability of recovery within 2 weeks was calculated as 44.62% based on the GMO-EE distribution, while Tanış [ 47 ] found it to be 45.25%.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the same dataset, Tanış [ 47 ] estimated the mean recovery time to be about 21 days, while Voinsky et al [ 48 ] reported an average recovery time of approximately 15 days for another sample of male COVID-19 patients over the age of 60 years (n = 582) and Barman et al [ 49 ] obtained the 95% confidence interval for average recovery time of 16 to 34 days based on another sample of COVID-19 patients (n = 221). The probability of recovery within 2 weeks was calculated as 44.62% based on the GMO-EE distribution, while Tanış [ 47 ] found it to be 45.25%. The results obtained from the GMO-EE distribution are thus supported by the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both in terms of distribution properties and statistical inference parallel to the study [11]. Tanış et al [13], introduced a transmutation lower record type and suggested a sub-model for Fréchet distribution, moreover Tanış [14], suggested transmutation lower record type inverse Rayleigh and Tanış [15], suggested transmutation lower record type power function distribution.…”
Section: Introductionmentioning
confidence: 88%